Microalgae Biotechnology as An Agent for Remediation and Improvement of Agricultural Soil Quality: A Systematic Literature Review - Ismi Farah Syarifah; Rizal Maulana Hasby; Dimas Ario Setiawan (Al Jahiz, 2026)
Agricultural soils are increasingly affected by contaminant accumulation, nutrient imbalance, and declining biological quality, while environmentally safer remediation strategies remain limited. This study synthesizes scientific evidence on the use of microalgae as biotechnological agents for the remediation and improvement of agricultural soil quality through a systematic literature review approach. A total of 17 eligible articles were selected through PRISMA 2020-based screening and analyzed qualitatively. The synthesis focused on the application forms of microalgae, their reported soil-related functions, and the limitations and future directions emerging from the current evidence base. The reviewed studies indicate that microalgae and microalgal products can contribute to pollutant removal, nutrient recovery, soil amendment, fertilizer substitution, biomass valorization, microbial community modulation, and biological soil improvement in agricultural systems. However, the available evidence remains limited and is still dominated by laboratory-scale, greenhouse, pot-based, and context-specific studies. Overall, microalgae represent promising but still developing biotechnological agents for sustainable soil remediation and quality improvement. Broader field validation, long-term assessment, safety evaluation, and scalability analysis are still needed before wider application in agricultural systems.